A computational model of an improved cooling radiant ceiling panel system for optimization and design. (October 2019) - Su, Xiaosong; Zhang, Ling; Liu, Zhongbing; Luo, Yongqiang; Lian, Jinbu; Luo, Yongwei
Abstract: Radiant cooling system comes to the foreground recently due to its improved thermal comfort and energy saving potential. However, surface condensation is still an unsolved problem and hinders the application of radiant cooling systems especially in hot and humid areas. An inside air layer was introduced to the improved cooling radiant ceiling panel (CRCP) system to achieve uniform temperature distribution on panel surface and reduce water condensation risk. A computational model for heat transfer analysis of the improved CRCP system was established and verified with experiment. The effects of the thickness of aluminum sheets, cooling panels and air layer, as well as the diameter and spacing of copper pipes on cooling capacity of the new system are studied. It is shown that the cooling capacity increases with thicker aluminum sheet and thicker radiant panel but thinner air layer. A thickness of 4.0–5.0 mm for the cooling panels is recommended to achieve a uniform surface temperature distribution according to numerical simulations. Besides, copper pipes with small diameter and thin plastic join are both beneficial to system performance. This study also provides a method to evaluate the maximum temperature difference and lowest surface temperature of the whole cooling panel, as well as a simple design chart for the improved CRCP system. Moreover, it is feasible to enhance the flow disturbance in air layer to improve heat transfer between the aluminum sheets and cooling panels, which can contribute to the savings of initial investment by using less pipe materials in CRCP. Highlights: A computational model of an improved cooling radiant ceiling panel system was established and verified. A method to evaluate the maximum temperature difference on cooling panels was proposed. The impact of flow disturbance inside air layer on system cooling capacity was revealed. Chart design method for the improved cooling radiant ceiling panel system was proposed.